Productivity of biotechnological sugar beet hybrids - Logvinov A. V.; Mischenko V. N.; Tsatsenko L. V.; Moiseev A. V. (E3S Web of Conferences, 2021)
A brief overview of the state of research on selection of new constant biotechnological lines – donors of glyphosate resistance and prospects of creating biotechnological hybrids of sugar beet are presented. Experimental data on nature of inheritance of glyphosate resistance in different sugar beet genotypes (mmSxxzz, mmNxxzz, MMTOp, etc.) were obtained. For the first time, separate and joint fruit lines-donors with 90-100% glyphosate resistance were obtained. In competitive and environmental tests, the first glyphosate-tolerant biotechnological hybrid of sugar beet TG-944 (1385) exceeded statistically the standard of yield and sugar volume from 1 ha. With mechanized (combine) harvesting, the average scoring yield of the hybrid was 65.5 t/ha. The purchasing costs for herbicides to protect sugar beet from weeds when growing glyphosate-resistant hybrids, compared to conventional commercial hybrids per 1 hectare on average for 2017-2019, amounted to 2447 and 8869 rubles, respectively, with an economic efficiency of 6422 rubles per 1 hectare of sowing.